(untitled) (Docentes 2.0 Journal, 2025)
The digital competence of university professors encompasses a set of knowledge, skills, attitudes, and practices that they must possess to effectively use digital technologies in their teaching, research, and academic management functions. The main objective of this study was to analyze the theoretical and methodological aspects and results of original research on digital competence in Latin American universities. The research was based on the systematic method, hermeneutic-interpretive paradigm, and qualitative approach, with a thematic narrative design of literary documentary type and longitudinal section. Searches were conducted in academic databases such as Scopus, Web of Science, SciElo, and Dialnet, covering studies published between 2019 and 2024 in Spanish and English. The results revealed considerable variability in the levels of digital competence among teachers in Latin America, which evidenced a significant gap between theory and practice in developing these skills. There was also evidence of increasing adoption and adaptation of various reference frameworks to standardize and improve teachers’ digital skills.